Inadvertent Prolonged Femoral Nerve Palsy After Field Block with Liposomal Bupivacaine for Inguinal Herniorrhaphy. Issue 11 (1st June 2016) - Olsen, David; Amundson, Adam; Kopp, Sandra
Abstract : Inguinal herniorrhaphy is a common outpatient procedure where analgesia can be augmented with local infiltration. We report a case of prolonged femoral nerve palsy secondary to liposomal bupivacaine use during wound infiltration after inguinal herniorrhaphy. Inadvertent transient femoral nerve palsy is a rare but known complication after ilioinguinal field block. This case both highlights the value of ultrasound imaging in evaluating the complications and demonstrates how the prolonged nature of liposomal bupivacaine can prolong adverse sequela.